Developing and evaluating security-aware software systems - Khan, Khaled M., 1959- (Information Science Reference, 2013)
"This book provides innovative ideas and methods on the development, operation, and maintenance of secure software systems and highlights the construction of a functional software system and a secure system simultaneously"-- Provided by publisher
Keywords: Computer networks -- Security measures.; Computer software -- Development.; Computer security.; elektronické knihy; electronic books